Političeskie aspekty vhoždeniâ stran Baltii v Bolonskij process - Nikiforov, Nikita (Political Aspects of Joining the Bologna Process by the Baltic States, 2011)
The article shows that the main driving forces of joining the Bologna Process by the Baltic states were: 1) the desire for preserving and increasing the intellectual potential by the improvement of national higher education systems in line with the Bologna recommendations, 2) preparing Latvia, Lithuania and Estonia to join the European Union as independent European states. Joining the Bologna Process was associated with a number of other pragmatic aspirations: the increase of competitive ability of national systems of higher education, the modernization of the organization, methods and technologies in higher education, joining the system of European academic mobility, the increase of employment prospects for graduates in the Baltic subsidiaries of European companies.
Keywords: Proces Boloński, kraje bałtyckie, Unia Europejska